Explanations on the global world geographical reality - José Armando Santiago-Rivera (Universidad del Magdalena, 2017)
This article reflects on the characteristics of the geographical situation of the current historical moment. It is assumed that geography teaching has overemphazed the descriptive tools over the problematizing ones that could lead to critically understanding the contemporary complexity. Methodologically, this assumption was determined by questioning ten (10) people studying geography teaching, to diagnose their perceptions on the issue. Their responses revealed their concerns about the complex globalized village accent; the weakness of education to understand the geographical situation and the need to promote critical explanation as an option to educate citizens on values. It is maintained that geographical education must be coherent with the times and must educate on values such as commitment and social responsibility in view of the difficult historical moment for contemporary society.